Analisis Morfometri Sub-DAS Lahundape Sebagai Penyebab Proses Sedimentasi di Teluk Kendari - Suryawan Asfar; Ali Okto; Andi Makkawaru; Isran Naim (Jurnal Rekayasa Geofisika Indonesia, 2020)
The Lahundape Sub-watershed is located in the area of Kendari City and Konawe District. Some of the problems that occur in the Kendari Bay region include siltation caused by sedimentary materials from all rivers that lead to Kendari Bay, one of which is the Lahundape River. One type of analysis that can be used to solve problems that arise is to do morphometric analysis. From the results of data processing and analysis found that the Lahundape Sub-watershed has a drainage density (Dd) of 11.6 km/km2, a very high stream frequency (Fs) value of 131.66, a drainage texture of 38.63, a factor of shape of 0.146 so that it can be grouped into elongated watersheds, roundness ratio values of 0.155 or Rc value <0.5, elongation ratio values of 0.216, surface flow lengths of 5.810 km, basin reliefs of 5.32 km or 5.324 meters, values of relief ratio of 0.77 and the roughness value of the Lahundape Sub-watershed is 61.82. So it can be concluded that the Lahundape Sub-watershed has a river flow that flows through rocks with soft resistance, so the transport of sediment transported will be greater than that the Lahundape Sub-watershed has sloping conditions that are quite sloping and high enough relief so it will tend to contribute on erosion and will later result in loss of sediment deposits in the sub-watershed area.